Prevention solution of iroet dry tea product damage at KSU XXX, Sukatani Village, Garut - Al Fattaah Muhammad Syah Fisabilillah (Research Institute for Tea and Cinchona, 2017)
One of dried tea product competitiveness can be seen from the quality of the tea. Therefore, to produce good quality tea is necessary to reduce the damage to dry tea. The implementation of Good Agricultural Practices (GAP) during the process of picking fresh tea leaves and Good Manufacturing Practices (GMP) during processing to produce dry tea is a way to obtain quality tea. This study aims to analyze the causes of damage to the tea during the production process and to find a preventive solution. A case study conducted on KSU XXX, Sukatani Village, District Cilawu, Garut regency producing Iroet tea. The research method used is a case study and used qualitative design. Some of the causes of damage occurring in the Iroet tea production process are the farmers' bad habits while picking tea shoots, carelessness of factory workers when sorting, and the production process activities are undertaken by the workers are inconsistent with GAP and GMP. Based on the three causes, the main cause of damage to Iroet tea products are workers who do not apply GAP and GMP during the production process, resulting in poor quality of the resulting tea. The solution to prevent the destruction of iroet tea products is to add one to three grading workers, and pay farmers shoots in accordance with the grading results.